Multi-objective Optimization of the Mobile Garbage Compression's Turnover Mechanism - Wen Hong; Wang Huqi; Liang Guangming; Zhang Yanqing (Jixie chuandong)
The hinge position of the turnover mechanism directly affects the overall working performance of the mobile garbage compression device and the working life of each hinge point of the turnover mechanism. To improve the overall working performance of the turnover mechanism and the working life of each hinge point, Adams software is used to establish a virtual prototype model and conduct simulation to obtain the load of each hinge point of the turnover mechanism. Then, the static strain tester is used to test the turnover mechanism, and it is found that the virtual prototype model conforms to the actual situation and has verified the validity of the model. On this basis, through further analysis of simulation data, the maximum load and minimum transmission angle of hinge point A and C of the tilting mechanism are determined as the optimization objectives. The ideal point method is applied to construct a comprehensive evaluation function in Adams software and solve it optimally. Through comparing the data before and after the optimization, the maximum load of hinge point A of the tilting mechanism is reduced by 19.3%, the maximum load of hinge point C is reduced by 16.2%, and the minimum transmission angle is increased by 32.1%. Finally, the optimal design value of the hinge position of the turnover mechanism is determined, which can provide reference for the subsequent design and application of the turnover mechanism of the mobile garbage compression device.